Sensitive men and hardy women: How do millennials, xennials and gen x manage to work from home? - Agota Giedrė Raišienė; Violeta Rapuano; Kristina Varkulevičiūtė (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Despite the huge number of studies on telework in 2020, the influence of socio-demographic characteristics of workers on their attitudes towards telework continues to raise questions. Researchers agree on some aspects, such as younger individuals being better at absorbing new technologies. However, given that not only those who wanted to but also those who were obliged to switched to teleworking, it appears that younger people may not be as effective at working remotely as previously thought. The relevance of our study is based on the contradictory findings of research conducted during the pandemic. With this article, we contribute to the accumulation of knowledge about the change that takes place in telework. The paper aims to examine the relationship between socio-demographic indicators and the evaluation of telework. Our study confirms that the gender and age of employees are important factors in an employee's attitude to telecommuting. Mostly, the attitudes vary in terms of gender. At least in the case of Lithuania where the research was conducted, Millennial men, unlike other generations and significantly more than Millennial women, see personal career development problems working remotely. Meanwhile, older generations do not declare greater dissatisfaction working remotely, although they do not express much favour for this approach. The results of the study indicate that in the circumstances created by the pandemic, organizations should update their human resource management strategies to achieve employee work efficiency and maintain employee motivation. The practical implication of our study in terms of open innovation is that in the future, the development of virtual working relationships will need to focus not on the technological training of older workers but on the specific provision of feedback to younger workers. In this regard, our insights may be useful for leaders in human resource management and open innovation teams.
Keywords: 650; COVID-19; Gen X; gender differences; Lithuania; Millennials; open innovation; telecommuting; work cohort; work from home; Xennials